Characteristics of current perception produced by intermediate-frequency contact currents in healthy adults - Uehara, Shintaro; Yuasa, Akiko; Ushizawa, Kazuki; Kodera, Sachiko; Kamimura, Yoshitsugu; Hirata, Akimasa; Otaka, Yohei (Frontiers in Neuroscience, 2023)
Introduction Contact electrical currents in humans stimulate peripheral nerves at frequencies of <100 kHz, producing sensations such as tingling. At frequencies above 100 kHz, heating becomes dominant, resulting in a sensation of warmth. When the current amplitude exceeds the threshold, the sensation results in discomfort or pain. In international guidelines and standards for human protection from electromagnetic fields, the limit for the contact current amplitude has been prescribed. Although the types of sensations produced by contact current at low frequencies, i.e., approximately 50–60 Hz, and the corresponding perception thresholds have been investigated, there is a lack of knowledge about those in the intermediate-frequency band—particularly from 100 kHz to 10 MHz. Methods In this study, we investigated the current-perception threshold and types of sensations for 88 healthy adults (range: 20–79 years old) with a fingertip exposed to contact currents at 100 kHz, 300 kHz, 1 MHz, 3 MHz, and 10 MHz. Results The current perception thresholds at frequencies ranging from 300 kHz to 10 MHz were 20–30% higher than those at 100 kHz (p < 0.001). In addition, a statistical analysis revealed that the perception thresholds were correlated with the age or finger circumference: older participants and those with larger finger circumferences exhibited higher thresholds. At frequencies of ≥300 kHz, the contact current mainly produced a warmth sensation, which differed from the tingling/pricking sensation produced by the current at 100 kHz. Discussion These results indicate that there exists a transition of the produced sensations and their perception threshold between 100 kHz and 300 kHz. The findings of this study are useful for revising the international guidelines and standards for contact currents at intermediate frequencies. Clinical trial registration https://center6.umin.ac.jp/cgi-open-bin/icdr_e/ctr_view.cgi?recptno=R000045660, identifier UMIN 000045213.